Rising inequality and stagnation in the US economy - Barry Z. Cynamon; Steven M. Fazzari (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
US household demand is well below its trend from prior to the Great Recession. We link weak demand to rising income inequality. The demand problem did not arise contemporaneously with higher income inequality because the bottom 95 percent of the income distribution went deeply into debt to maintain consumption growth despite their stagnant income growth. But we argue that the demand impact of greater inequality did appear in the aftermath of the recession. A calibrated Keynesian growth model shows that the lower income share of the bottom 95 percent can explain the deviation of the US economy from its pre-recession trend.
Keywords: D31; E01; E12; E21; 330; aggregate demand; consumption; saving; household; national income and product accounts